Performance Evaluation of the VITEK2 and Sensititre Systems to Determine Colistin Resistance and MIC for Acinetobacter baumannii - Hae-Sun Chung; Soo-Kyung Kim; Chorong Hahm; Miae Lee (Diagnostics, 2022)
Performances of the colistin antimicrobial susceptibility testing (AST) systems of Acinetobacter baumannii vary depending on the manufacturer, and data on colistin-resistant A. baumannii are limited. We evaluated the VITEK2 and Sensititre systems to determine colistin resistance and minimum inhibitory concentration (MIC) for A. baumannii isolated from a clinical microbiology laboratory. A total of 213 clinical A. baumannii isolates were tested, including 81 colistin-resistant A. baumannii. ASTs were performed using the VITEK2 and Sensititre systems according to the manufacturer’s instructions. Reference MICs for colistin were determined using the manual broth microdilution method (BMD). The results of the two AST methods were compared with the BMD results. VITEK2 and Sensititre systems showed category agreements of 95.3% and 99.1%, respectively. VITEK2 had a relatively high very major error (VME) rate (9.9%). Sensititre reported higher MICs than the reference method for the susceptible isolates and showed low essential agreement. In conclusion, the automated systems investigated in this study showed good category agreements for colistin AST of A. baumannii. However, VITEK2 had a high VME rate, and Sensititre had differences in MIC results. Colistin AST remains a challenging task in the clinical laboratory.